Short-term Effects of Laparoscopic Adjustable Gastric Banding Versus Roux-en-Y Gastric Bypass - Gastaldelli, Amalia; Iaconelli, Amerigo; Gaggini, Melania; Magnone, Maria Chiara; Veneziani, Augusto; Rubino, Francesco; Mingrone, Geltrude (Diabetes care, 2016)
Bariatric surgery has been shown to have important long-term metabolic effects resulting in enhanced insulin sensitivity and improved glucose tolerance in patients with type 2 diabetes. The contribution of reduced caloric intake to these beneficial effects of surgery remains unclear. The aim of this study was to compare the short-term effects (1 week) of bariatric surgical procedures with a very low caloric intake (VLCI) on insulin sensitivity (IS) and insulin secretion (ISR) in nondiabetic obese subjects. Twenty obese patients without diabetes (BMI 44.2 ± 0.7 kg/m ) were admitted to the clinic for 1 week. At baseline and 1 week after VLCI (600 kcal/day), subjects received a hyperinsulinemic-euglycemic clamp with tracer infusion to quantify endogenous glucose production (EGP), lipolysis (rate of appearance of glycerol [RaGlycerol]), peripheral insulin sensitivity (insulin-stimulated glucose disposal [M value] divided by the steady-state plasma insulin concentration [M/I]), hepatic insulin sensitivity (Hep-IS [= 1/(EGP ⋅ insulin)]), and adipose insulin sensitivity (Adipo-IS [= 1/(RaGlycerol ⋅ insulin)]). An intravenous glucose bolus was administered at the end of the insulin clamp to measure ISR and β-cell function (disposition index [DI]). Approximately 3 months later, patients were admitted for laparoscopic adjustable gastric banding (LAGB) (n = 10) or Roux-en-Y gastric bypass (RYGB) (n = 10), and were restudied 1 week after surgery under the same caloric regimen (600 kcal/day). After 1 week of VLCI, patients lost 2.1 kg without significant changes in Hep-IS, Adipo-IS, M/I, or DI. RYGB and LAGB led to greater weight loss (5.5 and 5.2 kg, respectively) and to significant improvement in Hep-IS, EGP, and lipolysis. Only RYGB improved Adipo-IS and M/I. No change in ISR or DI was observed in either surgical group. Bariatric surgery improves IS within 1 week. These metabolic effects were independent of caloric intake and more pronounced after RYGB compared with LAGB.